Inclusive deliberation for future-regarding governance: potentials and pitfalls - Setälä, Maija (Taylor and Francis Group, 2025)
Arguably, representative democracies are prone to "wrongful short-termism". This article examines the potential of democratic deliberation to enhance future-regarding governance and to avoid wrongful short-termism. I distinguish between three different types of democratic deliberation-"Habermasian", integrative, and inclusive-and examine their relative strengths and weaknesses in terms of future-regarding governance. I argue that specific designs for inclusive deliberation are likely to facilitate representation and consideration of future interests. This article reviews and evaluates existing institutional designs enhancing inclusive deliberation, especially deliberative mini-publics and parliamentary committees for the future, as well as proposals for randomly selected second chambers. The paper concludes that forums for inclusive deliberation have the potential to enhance consideration of future interests in representative systems and to help avoid wrongful short-termism. However, the evidence on the capacity of inclusive deliberation to enhance the empirical legitimacy of future-regarding governance in representative systems is still scarce and inconclusive.